Design and development of a multi-protocol and multi-function Datalogger for measuring hydric balance in a forest environment - Zarzosa M. (2020)
Currently, the use of different types of sensors and dataloggers (which use different communication protocols) could generate drawbacks to achieve adequate interoperability and scalability. In particular, for a solution applicable to precision agriculture, a specific purpose datalogger has been designed and developed, consisting of an ATMEL microcontroller (MCU), a micro SD memory, sensors with different communication protocols (UART, I2C, SDI 12), analog inputs, multilevel operating voltages. In order to achieve this goal, some complementary works had to be carried out: This solution has been tested in a PtM LoRa network composed of two sensor nodes and, in addition, the integration of this network with a commercial datalogger of Campbell brand has been made, with the mission of consolidating and storing the sensed data. According to the above, this article shows the design and development of this Datalogger optimized for its application in precision agriculture scenario. © 2020 IEEE.